English English: English - Muhammad Rafly (Journal of Informatics and Advanced Computing (JIAC), 2024)
Scholarship is an assistance program in the form of educational funding in the form of being given to assist students in obtaining proper education. SMA Negeri 8 Bogor City as an educational unit that organizes formal education, participates in providing scholarships for its students. The scholarship program at SMA Negeri 8 Bogor City has not used an effective and efficient method in determining the eligibility of students to receive scholarships so that errors often occur such as scholarships that are not on target. To overcome this, a website-based scholarship prediction application was created to predict the eligibility status of students to receive scholarships. Prediction is done using the classification method with the Support Vector Machine model. The results in the composition of 70% training data and 30% testing data get the highest evaluation results with Accuracy 89%, Precision 91%, Recall 95%.